Method for improving surface bonding strength of ultrahigh-temperature ceramic coating through additive coarsening

The adhesive layer and rough layer are provided on the surface of the ultra-high temperature ceramic coating by adding additive roughening methods, which solves the problem of difficult surface roughening of ultra-high temperature ceramic materials in the prior art, realizes high bonding between ceramic materials and other materials, and widens the use field of ceramic coatings.

CN120081692AActive Publication Date: 2025-06-03CENT SOUTH UNIV

Patent Information

Application Number
CN202510574584.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-06-03
Estimated Expiration
2045-05-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively roughen the surface of ultra-high temperature ceramic materials with high strength, high hardness, high melting point and significant brittleness, resulting in weak bonding with other materials and difficult to widely use in industry.

Method used

Through the additive roughening method, an adhesive layer is first provided on the surface of the ultra-high temperature ceramic coating, and then a rough layer is provided on the surface of the adhesive layer. The maximum surface height difference Ry range of the rough layer is controlled to be 0.15~0.5mm, and finally a sintering treatment is performed to obtain a rough ceramic coating with high binding force.

Benefits of technology

It significantly improves the firmness of the surface coating of ceramic materials with other materials, avoids the negative impact of the reduction and roughening process on the mechanical properties of the materials, does not depend on specific equipment and material growth characteristics, and has a wider application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081692A_ABST
    Figure CN120081692A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the surface bonding strength of an ultra-high-temperature ceramic coating through additive coarsening, and belongs to the technical field of ceramic coating preparation. Bonding layer slurry is arranged on the surface of the ultra-high-temperature ceramic coating to obtain a bonding layer, then rough layer slurry is arranged on the surface of the bonding layer to be coarsened to obtain a rough layer, and the rough layer is prepared into the ultra-high-temperature ceramic coating through additive coarsening. The maximum height difference Ry of the surface in the rough layer is controlled to range from 0.15 mm to 0.5 mm, and finally sintering treatment is conducted to obtain the rough ceramic coating. According to the method, the bonding firmness of the surface coating of the ceramic material and other materials can be remarkably improved, the possible negative influence of a subtractive roughening process on the mechanical property of the material is effectively avoided, meanwhile, the method does not depend on specific equipment and material growth characteristics, and therefore the method has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high-temperature ceramic surface roughening, and relates to a method for improving the surface bonding strength of ultra-high temperature ceramic coatings through additive roughening. Background Art

[0002] At present, with the rapid development of technology, a single type of material has become difficult to meet the increasingly diverse needs of various fields. Therefore, the method of compounding multiple materials has emerged. It can skillfully combine the excellent properties of different materials to meet the requirements of various complex application scenarios. However, between different types of materials, such as metal and ceramic, ceramic and polymer material, metal and polymer material, or between different types of ceramics, due to the differences in physical and chemical properties, the bonding force between them is relatively weak, making it difficult to effectively combine and use them together.

[0003] To solve this problem, it has been found that a rough surface is beneficial to improving the mechanical bonding force between materials with different physical and chemical properties. Therefore, surface roughening technology has become a key means to enhance the bonding force between materials. Among many surface roughening treatment methods, methods such as grinding with a carborundum bur, sandblasting, laser etching, and acid etching are widely used. These roughening methods are not only simple to operate but also extremely efficient, so they are widely used in industry.

[0004] However, these methods also have certain limitations. They adopt a subtractive method to achieve the roughening of the material surface. Such a treatment method often causes great damage to the material, easily leading to stress concentration and defect generation on the material surface. These defects will not only reduce the mechanical properties of the material but also affect the service life and reliability of the material. Moreover, for ceramic materials, especially ultra-high temperature ceramics such as tantalum carbide, hafnium carbide, and zirconium carbide, due to their high melting point, high hardness, and high brittleness, it is very difficult to achieve the roughening of the surface of these ultra-high temperature ceramic coatings through a subtractive method.

[0005] In addition to increasing surface roughness by subtractive methods, there are also some methods to roughen the surface through in-situ growth. For example, preparing rough hafnium nitride films by magnetron sputtering (Growth and Surface Roughening Mechanism of Smooth and Rough Hafnium Nitride Films), or roughening the surface of steel by electrolytic deposition (Fabrication of Roughened Electrodeposited Copper Coating on Steel for Dissimilar Joining of Steel and Thermoplastic Resin), etc. Although these methods can effectively improve the surface roughness of materials and thus enhance the bonding force between materials, they have relatively high requirements for the performance of equipment or the materials themselves. Therefore, it is difficult to promote them on a large scale on the surface of ceramic materials in practical applications. Summary of the Invention

[0006] Aiming at the problems in the prior art, such as the difficulty in roughening the surface of ultra-high temperature ceramic materials with high strength, high hardness, high melting point and significant brittleness, the purpose of the present invention is to provide a method for improving the surface bonding strength of ultra-high temperature ceramic coatings through additive roughening. The method of the present invention can not only significantly improve the bonding firmness between the surface coating of ceramic materials and other materials, but also effectively avoid the possible negative impact of subtractive roughening process on the mechanical properties of materials. At the same time, it does not depend on specific equipment and material growth characteristics, so it has a broader application prospect.

[0007] In order to achieve the above technical purpose, the present invention adopts the following technical solutions:

[0008] A method for improving the surface bonding strength of ultra-high temperature ceramic coatings through additive roughening, in which an adhesive layer slurry is set on the surface of the ultra-high temperature ceramic coating to obtain an adhesive layer, and then a rough layer slurry is set on the surface of the adhesive layer for roughening to obtain a rough layer. The range of the maximum surface height difference Ry in the rough layer is controlled to be 0.15 - 0.5 mm, and finally sintering treatment is carried out to obtain a rough ceramic coating;

[0009] The adhesive layer slurry contains metal powder and ultra-high temperature ceramic powder A; the mass fraction of the metal powder in the adhesive layer slurry is 30 - 60 wt%, and the mass fraction of the ultra-high temperature ceramic powder A in the adhesive layer slurry is 10 - 20 wt%;

[0010] The rough layer slurry contains ultra-high temperature ceramic powder B, and the mass fraction of the ultra-high temperature ceramic powder B in the rough layer slurry is 48 - 80 wt%;

[0011] The ultra-high temperature ceramic powder A in the adhesive layer slurry and the ultra-high temperature ceramic powder B in the rough layer slurry are of the same type of ultra-high temperature ceramic, and are each selected from at least one of carbides, oxides or borides of titanium, zirconium, niobium, vanadium, and tantalum.

[0012] In the present invention, the maximum surface height difference in the rough layer refers to the difference between the vertex of the convex part and the lowest point of the concave part of the rough layer within a certain area range (the measuring instrument is a 0918 roughness meter).

[0013] In the preparation method of the present invention, an adhesive layer is first provided on the surface of a substrate with an ultra-high temperature ceramic coating. During the sintering process, the metal powder in the adhesive layer slowly melts, enabling the ceramic particles of the rough layer and the ultra-high temperature ceramic coating to undergo mutual diffusion sintering through the metal liquid phase. The adhesive layer contains the same ultra-high temperature ceramic powder as that in the rough layer slurry, which can prevent the metal from flowing in the high-temperature liquid phase state and causing a large displacement of the rough layer morphology. Eventually, a rough ceramic coating with a rough morphology is obtained after sintering. Using this rough ceramic coating as a transition layer and continuing to introduce other heterogeneous materials on the basis of this transition layer, a layered composite coating with high bonding strength can be prepared, expanding the application field of the ceramic coating.

[0014] In the present invention, first, the amount of the metal powder in the bonding layer needs to be controlled within the scope of the present invention. If the addition amount is too large, there will be more residual metal impurities, affecting the coating purity and corrosion resistance at high temperatures. If the addition amount is too small, the liquid phase generated during the sintering process will be insufficient, resulting in insufficient densification of the ceramic sintering. The metal powder controlled within the scope of the present invention can promote ceramic sintering during the sintering process, volatilize in the high-temperature and low-pressure environment in the later stage of the sintering process, and finally be evacuated by a vacuum pump, thus not weakening the high-temperature mechanical properties of the ceramic coating during use. Second, the rough layer slurry is set on the surface of the adhesive layer, and the range of the maximum surface height difference Ry in the dried rough layer is 0.15 - 0.5 mm. If Ry < 0.15 mm, it is easy to cause peeling during the preparation process of the sintered transition layer and the further introduction of heterogeneous materials. If Ry > 0.5 mm, it will affect the subsequent coating surface morphology and component accuracy.

[0015] In a preferred embodiment, the ultra-high temperature ceramic coating is provided on the surface of the substrate, and the substrate is selected from one of graphite, carbon-carbon composite materials, and silicon carbide fiber-reinforced ceramic matrix composite materials.

[0016] During the actual operation process, before setting the adhesive layer slurry on the surface of the ultra-high temperature ceramic coating, it is necessary to clean the surface of the ultra-high temperature ceramic coating with acetone and ethanol in sequence.

[0017] In a preferred embodiment, the bonding layer slurry, by mass percentage, is composed of the following: 30-60 wt% of metal powder, 10-20 wt% of ultra-high temperature ceramic powder A, 0.5-2 wt% of binder, 0.5-2 wt% of dispersant, and 25-50 wt% of solvent.

[0018] In the present invention, the bonding layer is fixed on the surface of the smooth ceramic coating through a polymer binder. Controlling the formulation of the bonding layer slurry within the scope of the present invention results in the optimal bonding performance between the finally obtained rough transition layer and the heterogeneous material.

[0019] In a further preferred embodiment, in the bonding layer slurry, the metal in the metal powder is selected from at least one of nickel, chromium, cobalt, iron, and copper.

[0020] In a further preferred embodiment, in the bonding layer slurry, the binder is selected from at least one of polyvinyl butyral and ethyl cellulose.

[0021] In a further preferred embodiment, in the bonding layer slurry, the dispersant is selected from at least one of polyethylene glycol, polyethyleneimine, and ammonium polyacrylate.

[0022] In a further preferred embodiment, in the bonding layer slurry, the solvent is selected from at least one of absolute ethanol, xylene, toluene, acetone, and n-hexane.

[0023] During the actual operation process, the metal powder, ultra-high temperature ceramic powder, binder, dispersant, and solvent are weighed and ball-milled and mixed according to the designed ratio of the bonding layer slurry to prepare it.

[0024] In a preferred embodiment, the bonding layer slurry is applied on the surface of the ultra-high temperature ceramic coating by brushing or spraying, and then dried to obtain the bonding layer.

[0025] In a preferred embodiment, the thickness of the bonding layer is ≤5 μm, preferably 2 μm. The thickness of the bonding layer needs to be controlled within 5 μm. If the bonding layer is too thick, it will cause excessive metal residue and reduce the performance of the coating at high temperatures.

[0026] In a preferred embodiment, the ultra-high temperature ceramic powder A in the bonding layer is composed of ultra-high temperature ceramic powder A1 with a particle size of 100-500 nm and ultra-high temperature ceramic powder A2 with a particle size of 5-10 μm. By mass ratio, ultra-high temperature ceramic powder A1: ultra-high temperature ceramic powder A2 = 0.2-0.5.

[0027] In this preferred embodiment, the slurry of the bonding layer is composed of the above two ultra-high temperature ceramic powders with different particle sizes. On the one hand, it can improve the packing density of the powder, improve the density and strength of the rough particles or the coating during the sintering process. At the same time, different gradations can make the large particles swallow the small particles during the sintering process, increasing the roughness of the coating.

[0028] In a preferred embodiment, the rough layer slurry is disposed on the surface of the bonding layer for roughening by a method selected from brushing, plasma spraying, and 3D printing, preferably brushing.

[0029] Further preferably, when the rough layer slurry is set on the surface of the bonding layer for roughening by brushing, the rough layer slurry used is composed of the following by mass percentage: ultra-high temperature ceramic powder B 48-80wt%, organic binder 0.1-5wt%, dispersant 0.1-5wt%, metal adhesive 0.1-5wt%, solvent 15-50wt%; the organic binder is selected from at least one of polyvinyl butyral and ethyl cellulose, the dispersant is selected from at least one of polyethyleneimine, polyethylene glycol, and ammonium polyacrylate, the metal adhesive is selected from at least one of iron, cobalt, and nickel, and the solvent is selected from at least one of ethanol, ethylene glycol, xylene, toluene, n-hexane, and benzene; wherein the ultra-high temperature ceramic powder B is composed of an ultra-high temperature ceramic powder B1 with a particle size of 1-5μm and an ultra-high temperature ceramic powder B2 with a particle size of 15-20μm, and the mass ratio of the ultra-high temperature ceramic powder B1 to the ultra-high temperature ceramic powder B2 is 60-80:20-40.

[0030] The rough layer slurry also uses a grading of coarse and fine particle sizes. The coarse ceramic particles can form ceramic rough points in the rough ceramic coating. During the sintering process, these points will swallow up the smaller ceramic particles nearby through the Oswald ripening mechanism. The energy of large particles is lower than that of small particles. Small particles have high energy and higher solubility than large particles. Small particles dissolved at high temperature will redeposit on large particles to form larger ceramic particles, increasing the roughness of the coating.

[0031] In the actual operation process, after each component is mixed according to the designed ratio, ball milling and ultrasonic dispersion are performed to obtain the rough layer slurry used.

[0032] Further preferably, the brushing process is: first use a sponge brush to brush the rough layer slurry on the surface of the ultra-high temperature ceramic coating, and the brushing thickness is controlled to be 0.2 mm or less, and then use a texture pot to dip the rough layer slurry and roll it back and forth on the surface for 3-6 times, and finally use the tip of the bristle brush to dip the rough layer slurry and evenly press dense protrusions on the surface, and the point pressing density is 100-400 / cm 3 .

[0033] More preferably, the height difference between the protrusions and depressions on the surface of the textured tank is less than 0.3 mm.

[0034] More preferably, the tip of the bristle brush is dipped into the rough layer slurry in an amount of no more than 2 g each time, and is dipped into the slurry again after pressing each point 5-10 times.

[0035] In the present invention, first, a random rough texture is formed on the coating through the porous structure or uneven surface of the sponge brush and the texture roller. Subsequently, the tip of the hard brush head is used to dip into the rough layer slurry and repeatedly perform point pressing on the surface until a uniform and densely packed raised dots are formed on the entire surface. Through the above process, Ry can be controlled between 0.15 - 0.5 mm.

[0036] Further preferably, during the brushing process, the temperature is controlled at 80 - 120 °C. During the actual operation, the substrate is placed on a workbench with a temperature of 80 - 120 °C.

[0037] Further preferably, during the plasma spraying, the rough layer slurry used, by mass percentage, is composed as follows: ultra-high temperature ceramic powder B 54 - 80 wt%, dispersant 0.1 - 1 wt%, binder 0.1 - 1 wt%, volatile substance 5 - 10 wt%, solvent 14 - 40 wt%. The dispersant is selected from at least one of polyvinylpyrrolidone and polycarboxylic acid. The binder is selected from at least one of carboxymethyl cellulose and polyvinyl alcohol. The volatile substance is selected from at least one of PMMA microspheres, ammonium bicarbonate, and paraffin. The solvent is selected from at least one of deionized water, ethanol, and ethylene glycol. Among them, ultra-high temperature ceramic powder B is composed of ultra-high temperature ceramic powder B3 with a particle size of 500 nm - 3 μm and ultra-high temperature ceramic powder B4 with a particle size of 10 - 30 μm. By mass ratio, the mass ratio of ultra-high temperature ceramic powder B3 to ultra-high temperature ceramic powder B4 is 70 - 90:10 - 30; the ultra-high temperature ceramic powder B4 is spherical particles obtained by granulation.

[0038] In the present invention, the rough layer slurry suspension is prepared according to the above formula. In the rough layer slurry formula, a grading of two kinds of particles is adopted, and the coarse particles are spherical powders obtained by granulation. The spherical powders have high fluidity and can uniformly flow around the plasma spray nozzle flame during the plasma spraying process. During the spraying process, the finer powders will absorb the energy of the plasma flame and melt, while the larger particle powders have limited energy absorption driven by the high-speed flame and are difficult to melt. Therefore, crystal nuclei of rough sites are formed, and the subsequent melted small particles can attach to the crystal nuclei and grow slowly to form rougher sites.

[0039] Further preferably, during the plasma spraying, the physical and chemical droplet size is controlled at 20 - 50 μm, the plasma power is 30 - 100 KW, the spraying distance is 20 - 150 mm, the nozzle moving speed is 30 - 80 cm / s, the spraying times are 5 - 10 times, the temperature of the substrate is 20 - 200 °C, and the carrier gas is a mixed gas of Ar and H 2 and, by volume ratio, Ar:H 2 = 5 - 25.

[0040] By controlling the parameters of the plasma spraying within the scope of the present invention and cooperating with the ultra-high temperature ceramic powder in the slurry, a rough layer with a Ry range of 0.15 - 0.5 mm can be obtained.

[0041] Further preferably, when performing 3D printing, the rough layer slurry used is composed of, by mass percentage: 50 - 60% of ultra-high temperature ceramic powder B and 40 - 50% of additives; the additives are composed of, by mass percentage: 60 - 80% of main binder, 10 - 30% of backbone binder, 0.5 - 2% of sintering aid, and 1 - 10% of surfactant; wherein the main binder is selected from at least one of polyoxymethylene and thermoplastic elastomer (TPE), the backbone binder is selected from at least one of polystyrene and high-density polyethylene, the sintering aid is selected from at least one of nickel, cobalt, chromium, copper, and iron, and the surfactant is selected from stearic acid.

[0042] Further preferably, before 3D printing, first, a rough layer model is set on the surface of the substrate model according to the shape of the substrate model by computer-aided (CAD). The rough layer model is an array of wavy grooves and columnar protrusions interspersed between the wavy grooves. The wavelength of the wavy grooves is 1 - 5 mm, the amplitude is 0.1 - 0.5 mm, the diameter of the columnar protrusions is 0.3 - 0.8 mm, the height is 0.1 - 0.5 m, and the density of the columnar protrusions is 50 - 200 per cm 3 . The height of the columnar protrusion is the height of its own printing.

[0043] During the actual operation process, after setting the rough layer model on the surface of the substrate model according to the shape of the substrate model by computer-aided (CAD), the sliced file of the established model is imported into the 3D printer. Then, the rough layer slurry is mixed and kneaded in a mixer, granulated to obtain pellets, and the pellets are placed in the 3D printer for printing.

[0044] Preferably, the process of the sintering treatment is as follows: under vacuum conditions, first heat up at a heating rate of 1 - 10 °C / min to 1800 - 1900 °C, then introduce a protective atmosphere and heat up at a heating rate of 3 - 5 °C / min to 2000 - 2500 °C, and keep the temperature for 2 - 4 h under slightly positive pressure.

[0045] The sintering process of the present invention first heats up under vacuum conditions, which is conducive to the decomposition and removal of the polymer additive of the binder, and the subsequent volatilization of the metal powder in a high temperature and low pressure environment, and finally being extracted by a vacuum pump, and finally under a slightly positive pressure and within the insulation time of the present invention, the ultra-high temperature ceramic is sintered to obtain a rough transition layer. In the entire sintering process, the present invention needs to control the heating rate, because the polymer additive decomposes in the low temperature stage, and the sintering rate needs to be reduced, otherwise it is easy to cause defects such as bulging and cracks. The ceramic sintering additive liquefies in the medium temperature stage. If the temperature rises too fast, it is easy to cause the liquid sintering additive to not spread in time, making the sintering uneven, resulting in the internal stress of the prepared coating, which is not conducive to subsequent use. The final high temperature stage (2000-2500℃) is the stage of grain growth and pore healing, and the heating rate must be controlled. If the temperature rises too fast, it is easy to cause the grain growth rate to exceed the pore removal rate, and finally a large number of closed pores remain in the coating. In addition to controlling the heating rate, the final sintering and holding time must also be guaranteed, otherwise the coating roughness may decrease.

[0046] However, since the present invention adopts different methods to prepare the rough layer, the slurry of the rough layer is different, and the types of ceramics are different, during the sintering process under vacuum conditions, a gradient temperature increase program is set to better remove polymer additives, metal powders, etc., and the sintering uniformity is better.

[0047] Preferably, the thickness of the rough ceramic coating is 300-800 μm.

[0048] Compared with the prior art, the present invention has the following advantages:

[0049] 1. The present invention avoids the disadvantage of reduced material roughening resulting in decreased mechanical properties of the coating material, and can prepare a rough ceramic coating on the surface of a large component.

[0050] 2. The present invention can enhance the bonding force between the ceramic coating and other heterogeneous materials, can prepare a layered composite coating with high bonding force, and expand the application field of the ceramic coating.

[0051] 3. The present invention can design the composition of the rough ceramic coating according to the use requirements. It only requires that the material can be sintered densely at high temperature, and the material itself does not need to have other special properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a cross-sectional schematic diagram of a rough coating prepared by the method of the present invention, which, from bottom to top, respectively includes: a substrate (100), a smooth ceramic coating (200), an adhesive layer (300), and a rough ceramic coating (400).

[0053] Figure 2 This is a macroscopic image of the rough tantalum carbide coating prepared in Example 1.

[0054] Figure 3 Scanning electron microscope image of the surface of the rough tantalum carbide coating prepared in Example 1.

[0055] Figure 4 Scanning electron microscope image of the cross-section of the rough tantalum carbide coating prepared in Example 1.

[0056] Figure 5 Macroscopic image of the combination of the rough tantalum carbide coating prepared in Example 1 and the second-phase coating.

[0057] Figure 6 Macroscopic image of the coating peeling off after the coating prepared in Comparative Example 1 is combined with the second-phase coating. Detailed implementation manners

[0058] Example 1

[0059] This example provides a method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening. In this example, a brush coating process was specifically used to prepare a rough tantalum carbide coating on the surface of the tantalum carbide coating, including the following steps:

[0060] 1) The graphite substrate with a tantalum carbide coating was successively cleaned with acetone and alcohol on the coating surface. The size of the graphite substrate was 20×20×10 mm, and the thickness of the tantalum carbide coating was 100 μm.

[0061] 2) Mix metals nickel, chromium, and cobalt in a ratio of 2:3:5 to form a metal mixed powder. Mix fine tantalum carbide powder with a particle size range of 100 - 500 nm and coarse tantalum carbide powder with a particle size range of 5 - 10 μm in a mass ratio of 1:3 to obtain a tantalum carbide mixed powder. Mix the tantalum carbide mixed powder with the metal mixed powder to obtain a cermet powder. Then, using ethanol and xylene as solvents, polyvinyl butyral as a binder, polyethylene glycol, and polyethyleneimine as dispersants, ball milling was carried out together to obtain an adhesive layer slurry. In the adhesive layer slurry, by mass percentage, the composition is as follows: metal mixed powder 50%, tantalum carbide powder 10%, ethanol 20%, xylene 16%, polyvinyl butyral 2%, polyethylene glycol 1%, polyethyleneimine 1%;

[0062] 3) The ball-milled and uniformly mixed adhesive layer slurry was evenly brushed with a thin layer on the surface of the tantalum carbide coating using a fine brush and dried in an oven at 80°C for 30 minutes to obtain an adhesive layer with a thickness of 3 μm.

[0063] 4) Configure the slurry containing tantalum carbide powder as the rough layer slurry, where the tantalum carbide powder is composed of tantalum carbide fine powder with a particle size of 1 - 5 μm and tantalum carbide coarse powder with a particle size of 15 - 20 μm, and the mass ratio of the tantalum carbide fine powder to the tantalum carbide coarse powder is 75:25;

[0064] Weigh tantalum carbide powder, ethylene glycol, toluene, nickel, ethyl cellulose, and polyethylene glycol according to the mass ratio of 80:11:5:1:2:1 respectively, and use a ball mill jar to ball mill and mix them to configure the slurry;

[0065] 5) First, use a sponge brush to brush the rough layer slurry on the surface of the ultra-high temperature ceramic coating, and control the brushing thickness at 0.2 mm. Then, use a texture jar (the average height difference of the surface protrusions and depressions is about 0.25) to dip the rough layer slurry and roll it back and forth on the surface 4 times. Finally, use the pointed tip of a hard brush head to dip the rough layer slurry and evenly dot-press dense protrusions on the surface. The amount of rough layer slurry dipped by the pointed tip of the hard brush head each time is no more than 2 g. After dot-pressing 5 - 10 times, re-dip the slurry and repeat dot-pressing on the surface until a uniform dense dot-pressed protrusion (the average height of the protrusion is about 0.3 mm) is formed on the entire surface, and the density of the protrusions is 200 per cm 3 ;

[0066] 6) Finally, put the sample into an oven for drying. The drying process is to keep it at 70 °C for 1 h, then heat it up to 120 °C and keep it at this temperature for 30 min, then heat it up to 160 °C and keep it at this temperature for 1 h, and finally keep it at 190 °C for 1 h. The heating rate is 5 °C / min. After drying, a rough layer is obtained. Use a 0981 roughness meter to measure the rough layer (the average value measured from 15 groups of data at different positions on the coating surface), and the average maximum height difference Ry of its surface is 0.3 mm;

[0067] 7) Put the dried sample into a high-temperature furnace, heat it up to 300 °C at a heating rate of 10 °C / min, continuously evacuate, then heat it up to 800 °C at a heating rate of 2 °C / min, the negative pressure state pressure is 20,000 Pa, then heat it up to 1800 °C at a heating rate of 8 °C / min, the negative pressure state pressure is 50,000 Pa, then heat it up to 2300 °C at a heating rate of 3 °C / min, and the air pressure gradually rises to normal pressure. The air pressure at 2300 °C is slightly positive pressure, and the pressure is controlled by the argon gas flow rate. Keep it at this temperature for 2 h to obtain a rough tantalum carbide ceramic coating.

[0068] The macroscopic view of the surface of the obtained rough tantalum carbide ceramic coating sample is as Figure 2 shown. There are many convex points on the coating surface, and the thickness of the rough tantalum carbide ceramic coating is 500 μm.

[0069] Figure 3The figure shows the secondary electron morphology of the surface of a rough tantalum carbide ceramic coating sample. The coating surface is pitted, with many holes and protrusions, which can provide a barb structure to fix the second-phase coating.

[0070] Figure 4 The figure shows the secondary electron morphology of the cross-section of a rough tantalum carbide ceramic coating sample. The barb structure of the coating can be clearly observed in the cross-sectional view.

[0071] Example 2

[0072] This example provides a method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening. In this example, a suspension plasma spraying process was specifically used to prepare a rough ZrHfTiTaNbC high-entropy ceramic coating on the surface of the tantalum carbide coating, including the following steps:

[0073] 1) The graphite substrate with the tantalum carbide coating was successively cleaned with acetone and alcohol to clean the surface of the coating. The size of the graphite substrate was 20×20×10 mm, and the thickness of the tantalum carbide coating was 100 μm.

[0074] 2) Mix nickel, chromium, and cobalt evenly in a ratio of 2:3:5. Mix fine ZrHfTiTaNbC high-entropy ceramic powder with a particle size range of 100-500 nm and coarse ZrHfTiTaNbC high-entropy ceramic powder with a particle size range of 5-10 μm in a mass ratio of 1:4 to obtain a ZrHfTiTaNbC high-entropy ceramic mixed powder. Mix the ZrHfTiTaNbC high-entropy ceramic mixed powder with the metal mixed powder to obtain a cermet powder. Then, using ethanol and toluene as solvents, polyvinyl butyral as a binder, polyethylene glycol, and polyethyleneimine as dispersants, ball-mill them together to obtain an adhesive layer slurry. In the adhesive layer slurry, by mass percentage, the composition is as follows: metal mixed powder 50%, ZrHfTiTaNbC high-entropy ceramic powder 10%, ethanol 20%, xylene 16%, polyvinyl butyral 2%, polyethylene glycol 1%, polyethyleneimine 1%;

[0075] 3) Use a fine brush to evenly apply a thin layer of the ball-milled and mixed adhesive layer slurry on the surface of the tantalum carbide coating, and place it in an oven at 80°C for 30 minutes to dry, obtaining an adhesive layer with a thickness of 3 μm.

[0076] 4) Configure the slurry containing ZrHfTiTaNbC high-entropy ceramic powder as the rough layer slurry. The ZrHfTiTaNbC high-entropy ceramic powder is obtained by mixing fine powder with an average particle size of 0.8 μm and spherical powder of 20 μm in a mass ratio of 80:20. The spherical powder is obtained by granulating and spheroidizing the fine powder. Weigh ZrHfTiTaNbC high-entropy ceramic powder, water, ethanol, carboxymethyl cellulose, polycarboxylic acid, and PMMA microspheres according to the ratio of 65:18:8:1:1:7 by mass, and use a ball milling tank to ball mill and mix them to configure the slurry.

[0077] 5) Pour the configured slurry into the feeding cavity. Use a plasma power of 55 kW, a spraying distance of 70 mm, keep the substrate temperature at 150 °C, carrier gas flow rate: 3 slpm (Ar / H 2 =50 / 5), control the physical and chemical droplet size to be 20 - 50 μm during plasma spraying, the nozzle moving rate is 35 cm / s, and the spraying times are 6 times.

[0078] 6) Finally, put the sample into an oven for drying. The drying process is to keep it at 50 °C for 1 h, heat it up to 100 °C and keep it for 2 h, slowly heat it up to 140 °C at a rate of 1 °C / min and then keep it for 2 h, and finally keep it at 180 °C for 1 h. The other heating rate is 5 °C / min. After drying, a rough layer is obtained. Use a 0981 roughness meter to measure the rough layer (the average value measured from 15 groups of data at different positions on the coating surface), and the average maximum height difference Ry on its surface is 0.3 mm.

[0079] 7) Put the dried sample into a high-temperature furnace. Heat it up to 180 °C at a heating rate of 5 °C / min, continuously evacuate, heat it up to 300 °C at a heating rate of 10 °C / min, continuously evacuate, heat it up to 900 °C at a heating rate of 2 °C / min, the negative pressure state pressure is 20,000 Pa, heat it up to 1600 °C at a heating rate of 8 °C / min, the negative pressure state pressure is 30,000 Pa, heat it up to 1900 °C at a heating rate of 5 °C / min, the negative pressure state pressure is 50,000 Pa, heat it up to 2500 °C at a heating rate of 3 °C / min, gradually increase the air pressure to normal pressure, the air pressure at 2500 °C is slightly positive pressure, and the pressure is controlled by the argon gas flow rate. Keep it for 2 h to obtain a rough tantalum carbide ceramic coating.

[0080] Example 3

[0081] This example provides a method for improving the surface bonding strength of ultra-high temperature ceramic coatings through additive coarsening. In this example, a 3D printing process is specifically used to prepare a rough zirconium boride ceramic coating on the surface of a zirconium boride coating, including the following steps:

[0082] 1) Clean the surface of the graphite substrate with zirconium boride coating successively using acetone and alcohol. The size of the graphite substrate is 20×20×10 mm, and the thickness of the zirconium boride coating is 100 μm.

[0083] 2) Mix metallic nickel, chromium, and cobalt in a ratio of 2:3:5 to form a metallic mixed powder. Mix fine zirconium boride powder with a particle size range of 100 - 500 nm and coarse zirconium boride powder with a particle size range of 5 - 10 μm in a mass ratio of 1:5 to obtain a zirconium boride mixed powder. Mix the zirconium boride mixed powder with the metallic mixed powder to obtain a cermet powder. Then, using ethanol and xylene as solvents, polyvinyl butyral as a binder, polyethylene glycol, and polyethyleneimine as dispersants, conduct ball milling together to obtain an adhesive layer slurry. In the adhesive layer slurry, by mass percentage, the composition is as follows: metallic mixed powder 50%, zirconium boride powder 10%, ethanol 20%, xylene 16%, polyvinyl butyral 2%, polyethylene glycol 1%, and polyethyleneimine 1%.

[0084] 3) Use a fine brush to evenly apply a thin layer of the adhesive layer slurry on the surface of the zirconium boride coating for the ball-milled and evenly mixed adhesive layer slurry, and place it in an oven at 80°C for drying for 30 minutes to obtain an adhesive layer with a thickness of 3 μm.

[0085] 4) Configure a 3D printing zirconium boride particle feedstock. Weigh zirconium boride particles and additives according to the designed ratio. The mass ratio of zirconium boride particles to additives is 60:40. Among the additives, by mass percentage, nickel is 1%, polystyrene is 25%, stearic acid is 5%, and polyoxymethylene is 69%. First, conduct dry ball milling of the zirconium boride and nickel powders for 12 h with a ball-to-material ratio of 6:1, then conduct high-temperature calcination at 1000°C, ball milling and crushing, and screening through a 300-mesh sieve to obtain a mixed powder. Add the mixed powder to a mixer at 110°C, maintain the rotation speed at 5 r / min, and mix for 1 h. Then add polystyrene and stearic acid to the mixer for mixing. At this time, adjust the temperature of the mixer to 190°C and mix at a rotation speed of 15 r / min for 2 h. Finally, add polyoxymethylene to the mixer and mix at a rotation speed of 50 r / min for 30 min. Put the well-mixed mass into a granulator to obtain 2-mm particle feedstock.

[0086] 5) Use computer-aided (CAD) to add transverse wavy grooves (wavelength 3 mm, amplitude 0.4 mm) and randomly interspersed columnar protrusions (diameter 0.6 mm, height 0.3 m) on the surface of the substrate model, and control the density of the columnar protrusions to be 100 / cm 3 , to obtain a three-dimensional geometric model with special regular protrusions and depressions.

[0087] 6) Add the prepared feedstock into the hopper of the 3D printer. The feedstock is fed through a screw into a heating barrel and heated to a molten state. Subsequently, it is deposited on the surface of the sample on the hot bed under the constraint of a nozzle according to the three-dimensional geometric model. The temperature of the heating barrel is 195 °C, the temperature of the hot bed is 150 °C, and the extrusion rate is 2 g / cm 3 , the printing rate is 50 mm / s, and the layer thickness is 0.1 mm.

[0088] 6) Place the printed sample into an atmosphere furnace for drying. The drying process is to keep it at 120 °C for 2 h, and it is protected by nitrogen throughout the process. After drying, a rough layer is obtained. Use a roughness meter 0981 to measure the rough layer (the average value measured from 15 groups of data at different positions on the coating surface), and the average maximum height difference Ry on its surface is 0.25 mm.

[0089] 7) Place the dried sample into a high-temperature furnace. Heat it at a heating rate of 5 °C / min to 900 °C, continuously evacuate, heat it at a heating rate of 2 °C / min to 1200 °C, continuously evacuate, heat it at a heating rate of 5 °C / min to 1500 °C, the pressure in the negative pressure state is 50,000 Pa, heat it at a heating rate of 8 °C / min to 1800 °C, the pressure in the negative pressure state is 80,000 Pa, heat it at a heating rate of 5 °C / min to 2000 °C, and gradually increase the air pressure to normal pressure. The air pressure at 2000 °C is slightly positive pressure, and the pressure is controlled by the nitrogen flow rate, and keep it at this temperature for 2 h to obtain a rough zirconium boride ceramic coating.

[0090] Comparative Example 1

[0091] Compared with Example 1, the difference is that during the process of step 5, a roller brush, sponge patting, and brush dotting are not used, and a brush coating is directly used to further prepare a uniform and smooth tantalum carbide coating on the surface of the transition layer.

[0092] Take the products obtained from the example and Comparative Example 1 as the substrates, and use the thermal spraying technology to prepare a YSZ thermal barrier coating with a thickness of 1 mm on their surfaces, and test the bonding strength between the YSZ coating and the rough coating in the example or the smooth ceramic coating generated in Comparative Example 1. The obtained bonding strength is shown in Table 1.

[0093] Figure 5 As shown, it is a YSZ thermal barrier coating prepared on the surface of the rough tantalum carbide coating prepared in Example 1 as the substrate using the thermal spraying technology. It can be seen from the macroscopic view that the surface of the YSZ coating is smooth and defect-free.

[0094] Figure 6The YSZ thermal barrier coating prepared by thermal spraying on the surface of the smooth tantalum carbide coating in Comparative Example 1. From the macroscopic view, it can be clearly seen that the YSZ coating cannot adhere to the surface of the smooth tantalum carbide coating, and partial peeling occurs in some areas. This is due to the difference in thermal expansion coefficient and chemical properties between the two coatings, resulting in poor bonding between the coatings and causing partial peeling of the YSZ coating on the surface of the tantalum carbide coating.

[0095]

[0096] Among them, the tensile strength of the graphite matrix is between 6 - 8 MPa.

[0097] Comparative Example 2

[0098] Compared with Example 1, the difference is that steps 2 and 3 are not carried out, that is, a thin bonding layer is not prepared on the surface of the smooth coating. As a result, the rough particles on the surface of the rough tantalum carbide ceramic after high-temperature sintering are prone to peeling. After spraying the YSZ coating on its surface by thermal spraying, the coating does not crack or peel off, but the bonding strength between the coatings is less than 3 MPa.

[0099] As mentioned above, only the preferred embodiments of the present invention are described, and there is no limitation to the present invention in any form or substance. It should be pointed out that for those of ordinary skill in the art in this technical field, without departing from the method of the present invention, several improvements and supplements can still be made, and these improvements and supplements should also be regarded as the protection scope of the present invention. Those skilled in the art, without departing from the spirit and scope of the present invention, when making some equivalent changes, modifications and evolutions using the technical content disclosed above, are all equivalent embodiments of the present invention; at the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solutions of the present invention.

Claims

1. A method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening, characterized in that: The bonding layer slurry is placed on the surface of the ultra-high temperature ceramic coating to obtain a bonding layer, and then the rough layer slurry is placed on the surface of the bonding layer to roughen the surface to obtain a rough layer, and the maximum height difference Ry of the rough layer is controlled to be in the range of 0.15-0.5 mm, and finally a sintering treatment is performed to obtain a rough ceramic coating; The bonding layer slurry contains metal powder and ultra-high temperature ceramic powder A; wherein the mass fraction of the metal powder in the bonding layer slurry is 30-60wt%, and the mass fraction of the ultra-high temperature ceramic powder A in the bonding layer slurry is 10-20wt%; The rough layer slurry contains ultra-high temperature ceramic powder B, and the mass fraction of the ultra-high temperature ceramic powder B in the rough layer slurry is 48-80wt%; The ultra-high temperature ceramic powder A in the bonding layer slurry and the ultra-high temperature ceramic powder B in the rough layer slurry are of the same type of ultra-high temperature ceramic, both of which are carbides, oxides or borides of at least one of titanium, zirconium, vanadium, niobium and tantalum.

2. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1, characterized in that: The ultra-high temperature ceramic coating is arranged on the surface of a substrate, and the substrate is selected from one of graphite, carbon-carbon composite materials, and silicon carbide fiber-reinforced ceramic-based composite materials.

3. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1, characterized in that: The bonding layer slurry is composed of the following by mass percentage: 30-60wt% metal powder, 10-20wt% ultra-high temperature ceramic powder A, 0.5-2wt% binder, 0.5-2%wt% dispersant, and 25-50wt% solvent; In the bonding layer slurry, the metal in the metal powder is selected from at least one of nickel, chromium, cobalt, iron and copper; In the adhesive layer slurry, the binder is selected from at least one of polyvinyl butyral and ethyl cellulose; In the adhesive layer slurry, the dispersant is selected from at least one of polyethylene glycol, polyethylene imine, and ammonium polyacrylate; In the adhesive layer slurry, the solvent is selected from at least one of anhydrous ethanol, xylene, toluene, acetone and n-hexane.

4. A method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1 or 3, characterized in that: The bonding layer slurry is disposed on the surface of the ultra-high temperature ceramic coating by brushing or spraying, and dried to obtain the bonding layer; The thickness of the adhesive layer is ≤5 μm; The ultrahigh temperature ceramic powder A in the bonding layer is composed of ultrahigh temperature ceramic powder A1 with a particle size of 100-500 nm and ultrahigh temperature ceramic powder A2 with a particle size of 5-10 μm. The mass ratio of ultrahigh temperature ceramic powder A1:ultrahigh temperature ceramic powder A2 is 0.2-0.

5.

5. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1, characterized in that: The method of setting the rough layer slurry on the surface of the bonding layer for roughening is selected from one of brushing, plasma spraying, and 3D printing.

6. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 5, characterized in that: When the rough layer slurry is set on the surface of the bonding layer for roughening by brushing, the rough layer slurry used is composed of the following by mass percentage: ultra-high temperature ceramic powder B 48-80wt%, organic binder 0.1-5wt%, dispersant 0.1-5wt%, metal binder 0.1-5wt%, solvent 15-50wt%; the organic binder is selected from at least one of polyvinyl butyral and ethyl cellulose, the dispersant is selected from at least one of polyethyleneimine, polyethylene glycol, and ammonium polyacrylate, the metal binder is selected from at least one of iron, cobalt, and nickel, and the solvent is selected from at least one of ethanol, ethylene glycol, xylene, toluene, n-hexane, and benzene; wherein the ultra-high temperature ceramic powder B is composed of ultra-high temperature ceramic powder B1 with a particle size of 1-5μm and ultra-high temperature ceramic powder B2 with a particle size of 15-20μm, and the mass ratio of the ultra-high temperature ceramic powder B1 to the ultra-high temperature ceramic powder B2 is 60-80:20-40; The brushing process is as follows: first, use a sponge brush to brush the rough layer slurry on the surface of the ultra-high temperature ceramic coating, and the brushing thickness is controlled to be 0.2 mm or less, and then use a texture pot to dip the rough layer slurry and roll it back and forth on the surface for 3-6 times, and finally use the tip of a hard bristle brush to dip the rough layer slurry and evenly press the surface to form dense protrusions; The height difference between the convex and concave surfaces of the textured tank is less than 0.3 mm; The tip of the bristle brush should be dipped into the rough layer slurry no more than 2g each time, and each point should be pressed 5-10 times before being dipped into the slurry again; During the brushing, the temperature is controlled at 80-120°C.

7. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 5, characterized in that: During the plasma spraying, the rough layer slurry used is composed of the following by mass percentage: ultra-high temperature ceramic powder B54-80wt%, dispersant 0.1-1wt%, binder 0.1-1wt%, volatile substance 5-10wt%, solvent 14-40wt%, the dispersant is selected from at least one of polyvinyl pyrrolidone and polycarboxylic acid, the binder is selected from at least one of carboxymethyl cellulose and polyvinyl alcohol, the volatile substance is selected from at least one of PMMA microspheres, ammonium bicarbonate and paraffin, and the solvent is selected from at least one of deionized water, ethanol and ethylene glycol, wherein the ultra-high temperature ceramic powder B is composed of ultra-high temperature ceramic powder B3 with a particle size of 500nm-3μm and ultra-high temperature ceramic powder B4 with a particle size of 10-30μm, and the mass ratio of the ultra-high temperature ceramic powder B3 to the ultra-high temperature ceramic powder B4 is 70-90:10-30; the ultra-high temperature ceramic powder B4 is spherical particles obtained by granulation; During the plasma spraying, the size of the physical and chemical droplets is controlled to be 20-50 μm, the plasma power is 30-100 KW, the spraying distance is 20-150 mm, the nozzle moving speed is 30-80 cm / s, the number of spraying times is 5-10 times, the temperature of the substrate is 20-200° C., and the carrier gas is a mixed gas of Ar and H2, and the volume ratio is Ar:H2=5-25.

8. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 5, characterized in that: During the 3D printing, the rough layer slurry used is composed of the following by mass percentage: 50-60% of ultra-high temperature ceramic powder B and 40-50% of additives; the additives are composed of the following by mass percentage: 60-80% of main binder, 10-30% of backbone binder, 0.5-2% of sintering aid, and 1-10% of surfactant; wherein the main binder is selected from at least one of polyoxymethylene and thermoplastic elastomer, the backbone binder is selected from at least one of polystyrene and high-density polyethylene, the sintering aid is selected from at least one of nickel, cobalt, chromium, copper, and iron, and the surfactant is selected from stearic acid; Before the 3D printing, a rough layer model is set on the surface of the base model according to the shape of the base model by computer aid. The rough layer model is an array of wave grooves and columnar protrusions interspersed between the wave grooves. The wavelength of the wave grooves is 1-5 mm, the amplitude is 0.1-0.5 mm, the diameter of the columnar protrusions is 0.3-0.8 mm, the height is 0.1-0.5 m, and the density of the columnar protrusions is 50-200 / cm 3 .

9. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1, characterized in that: The sintering process is as follows: under vacuum conditions, firstly heating the temperature to 1800-1900°C at a heating rate of 1-10°C / min, then introducing a protective atmosphere and heating the temperature to 2000-2500°C at a heating rate of 3-5°C / min, and keeping the temperature under a slight positive pressure for 2-4 hours.

10. The method for improving the surface bonding strength of ultra-high temperature ceramic coatings by additive roughening according to claim 1, characterized in that: The thickness of the rough ceramic coating is 300-800 μm.

Citation Information

Patent Citations

  • High-entropy oxide ultrahigh-temperature thermal barrier coating prepared by using APS technology and method thereof

    CN114000089A

  • Preparation method of temperature-sensitive functional gradient environmental barrier coating of high-entropy principal component integrated phosphorescent ions

    CN118851801A

  • Method for preparing porous tantalum carbide ceramic by combining template method with carbon thermal reduction method

    CN119751072A

  • Producing tantalum carbide layer on technical ceramics using a spray coating and high-temperature sintering process based on aqueous solutions

    EP4186881A1

  • Yttria-coated ceramic components of semiconductor material processing apparatuses and methods of manufacturing the components

    US20050136188A1

Cited By

  • Multi-layer composite ceramic coating with high-temperature stability and corrosion resistance on graphite surface and preparation method of multi-layer composite ceramic coating

    CN120483774A